Service quality management based on the application of the itil standard (2014)
The modern world has led companies to become increasingly competitive, highlighting the customer as the core element of commercialization processes, and also recognizing the need to treat all internal activities as customers in the delivery of products/services to final consumers. An important element to ensure an adequate level of customer satisfaction is the need to properly manage the required services inside business processes, where the management of technology services becomes an imperative in almost every company. This paper presents the ITIL standard, which is a framework that allows the delivery of technology services to be efficiently managed, in order to improve internal business processes and obtain other benefits such as better internal communication. After that, the use of ITIL as a frame of reference for enhancing quality is proposed, focused not only on IT but on any type of service in general.